Biosynthetic Machinery Involved in Aberrant Glycosylation: Promising Targets for Developing of Drugs Against Cancer - Vasconcelos-dos-Santos, Andréia; Oliveira, Isadora A.; Lucena, Miguel Clodomiro; Mantuano, Natalia Rodrigues; Whelan, Stephen A.; Dias, Wagner Barbosa; Todeschini, Adriane Regina (Frontiers in Oncology, 2015)
Cancer cells depend on altered metabolism and nutrient uptake to generate and keep the malignant phenotype. The hexosamine biosynthetic pathway (HBP) is a branch of glucose metabolism that produces UDP-GlcNAc, and its derivatives, UDP-GalNAc and CMP-Neu5Ac, donor substrates used in the production of glycoproteins and glycolipids. Growing evidence demonstrates that alteration of the pool of activated substrates might lead to different glycosylation and cell signaling. It is already well established that aberrant glycosylation can modulate tumor growth and malignant transformation in different cancer types. Therefore, biosynthetic machinery involved in the assembly of aberrant glycans are becoming prominent targets for anti-tumor drugs. This review describes three classes of glycosylation, O-GlcNAcylation, N-linked and mucin type O-linked glycosylation, involved in tumor progression, their biosynthesis and highlights the available inhibitors as potential anti-tumor drugs.